2002
DOI: 10.1034/j.1600-9657.2002.180106.x
|View full text |Cite
|
Sign up to set email alerts
|

Vertical root fracture treated by bonding fragments and rotational replantation

Abstract: These case reports describe a new treatment method for complete vertical root fractures. This method is composed of two steps. First, the fractured tooth is intentionally extracted atraumatically, and then the separated fragments are bonded with an adhesive resin cement. The restored tooth is replanted by rotating approximately 180 degrees into the original socket and fixing with an orthodontic wire. For both cases reported here, bone regeneration was observed at the 3-year follow-up. Since this modality adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 11 publications
0
59
0
2
Order By: Relevance
“…This resin was chosen because of reports stating that inflammation of periodontal ligament did not occur histopathologically after bonding of the fracture gap with Super Bond [11,13], and also because of a number of clinical reports [5][6][7][8][9] describing good outcomes when Super Bond was used to treat vertically fractured roots. Super Bond uses tri-n-butyl borane as a polymerization initiator, so when it comes in contact with moisture, radicals are generated and polymerization progresses [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This resin was chosen because of reports stating that inflammation of periodontal ligament did not occur histopathologically after bonding of the fracture gap with Super Bond [11,13], and also because of a number of clinical reports [5][6][7][8][9] describing good outcomes when Super Bond was used to treat vertically fractured roots. Super Bond uses tri-n-butyl borane as a polymerization initiator, so when it comes in contact with moisture, radicals are generated and polymerization progresses [14].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, if the tooth is single-rooted, the tooth is extracted, and if it has multiple roots, the root involved is resected or hemisection is performed [1][2][3][4]. A number of studies have described efforts to clinically preserve teeth, with particular success reported with resin bonding [5][6][7][8][9]. Sugaya et al used 4-methacryloxyethyl trimellitate anhydride/methyl methacrylate tri-n-butyl borane (4-META/MMA-TBB) resin to bond 23 teeth with vertically fractured roots, performing bonding either through the root canal or with the intentional replantation method, and reported after 6 to 74 months of observation that 18 (78%) of the teeth could be preserved [5].…”
Section: Introductionmentioning
confidence: 99%
“…This has been tried by first extracting the tooth and following bonding, re-implanting it back into the socket. 36 An alternative technique involving bonding through the root canal has also been described. 37 Whilst these preliminary studies have given optimistic results the reality is that the poor prognosis remains and there are more predictable ways of replacing missing teeth such as bridges and implants.…”
Section: Vertical Root Fracturementioning
confidence: 99%
“…Methods of extraction, bonding the fractured segments, and replantation of the bonded segments that are similar to those of Trope et al 11) have been used in many recent studies, [12][13][14][15][16][17] in which bonding resin and resin cement were used to fix the fractured teeth segments instead of glass-ionomer cement. The 4-META/MMA-TBB resin cement (Super-Bond C&B, Sun Medical, Kyoto, Japan) is the most frequently used type of resin cement, as it has been reported to have superior biocompatibility.…”
Section: ⅰ Introductionmentioning
confidence: 99%